2017
DOI: 10.3390/app7040407
|View full text |Cite
|
Sign up to set email alerts
|

Self-Referenced Spectral Interferometry for Femtosecond Pulse Characterization

Abstract: Abstract:Since its introduction in 2010, self-referenced spectral interferometry (SRSI) has turned out to be an analytical, sensitive, accurate, and fast method for characterizing the temporal profile of femtosecond pulses. We review the underlying principle and the recent progress in the field of SRSI. We present our experimental work on this method, including the development of self-diffraction (SD) effect-based SRSI (SD-SRSI) and transient-grating (TG) effect-based SRSI (TG-SRSI). Three experiments based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Nowadays, the Self-Referenced Spectral Interferometry (SRSI) 13 is a popular method for determining the time evolution of ultrashort optical pulses. It is based on the interference of an unknown pulse and a self-created reference pulse, which is generated by a third-order nonlinear optical effect 14 .…”
Section: Pacs Numbers: Valid Pacs Appear Herementioning
confidence: 99%
“…Nowadays, the Self-Referenced Spectral Interferometry (SRSI) 13 is a popular method for determining the time evolution of ultrashort optical pulses. It is based on the interference of an unknown pulse and a self-created reference pulse, which is generated by a third-order nonlinear optical effect 14 .…”
Section: Pacs Numbers: Valid Pacs Appear Herementioning
confidence: 99%
“…The self-referenced spectral interferometry (SRSI) technique has been recognized as a potent methodology for characterizing the temporal-spectral properties of femtosecond laser pulses. It boasts notable advantages such as singleshot operation, self-referencing, simplicity in optical setup, rapid measurement, and analytical iteration [1] . This technique has been employed for characterizing pulses with durations nearing 10 fs [2] and energies below 0.5 nJ [3] .…”
Section: Introductionmentioning
confidence: 99%
“…The principle is based on Spectral Domain Interferometry (SDI). SDI combined with Fourier analysis is a powerful metrology tool, already developed for optical coherent tomography [26], bulk group index measurement [27], phase response of metasurfaces [28] or ultrashort pulse characterization [29,30]. In previous publications, we have shown that common-path SDI performed with femtosecond pulses is suitable to achieve real-time tracking of the electro-optical changes in birefringence of nematics [3,11].…”
Section: Introductionmentioning
confidence: 99%